A diversidade de sentidos nas páginas Papel Pop e Popline no período eleitoral de 2018: embates e debates sobre questões LGBTQIA+ - Riboli, Milena (Universidade do Vale do Rio dos Sinos, 2021)
This research aims to analyze the sense production generated in the comments left on Facebook in posts from Papel Pop and Popline's pages during September and November of 2018. A data collection of the most engaged posts from both mediatic vehicles from the month before, the month during and the month after the presidential elections of that year was gathered in worksheets. With the constant menaces to human rights and democracy implied by Jair Bolsonaro's campaign proposals, the atmosphere in social media was of tension and multiple attempts to revert the probable resulting scenario. The ten posts with the most reactions were selected, reuniting five posts from each page. In exhaustive data collection, near six thousand comments pertaining to the total ten posts were read, categorized and selected in order to bring to the analysis the most controversial, engaged, incoherent and liked so we could break down the senses emanated by them using a combination of two methodologies: Content Analysis and Analysis of Sense Construction in Digital Networks. A total of 29 categories were perceived for the analysis of the ten posts. The categories helped us in understanding the senses produced by the comments left in the network.
Keywords: Cultura pop; Redes sociais; Produção de sentidos; Comunidade LGBTQIA+; Pop culture; Social networks; Sense production; LGBTQIA+ community; ACCNPQ::Ciências Sociais Aplicadas::Comunicação